Hi-tech windows in the aircraft cabin: The impact of display latencies on passengers' comfort. (May 2020) - Stelling, Dirk; Hermes, Michael; Huelmann, Gerrit; Mittelstädt, Justin; Niedermeier, Dominik; Schudlik, Kevin; Duda, Holger
Abstract: Hi-tech cabin windows offer exciting opportunities for future aviation industry for cost and design reasons. However, little is known about how displays replacing real windows in an airplane influence passenger comfort. Research here mainly focusses on pilots in flight simulators or not flight-related laboratory virtual environments but not on passengers. One result in these studies is that display latencies may cause symptoms of sickness which can be a crucial factor for comfort. Therefore, the purpose of the present study is to evaluate the impact of latency on passengers' comfort. 104 participants were recruited as passengers in a full-motion cabin simulator with high-resolution digital displays as hi-tech cabin windows. In three flights the delay between actual motion of the cabin and windows' outside view was varied (0/0.5/10 s) and four flight segments (take-off, cruise, turbulence and approach) were compared. Inflight and post-flight measures of sickness and estimates of realness were analyzed. Results indicate that only a latency of 10 s had an impact on sickness. Moreover, sickness was mostly characterized by oculomotor symptoms. Inflight measurements revealed that the first flight segments (take-off and cruise) were less affected by long latency than the last flight segments (turbulence and approach). Participants who rated the situation as unreal suffered more from sickness; seating position had no impact on the ratings. The study showed that small latency is a negligible problem for passengers and hi-tech outside view is suitable for future mobility. Highlights: Hi-tech windows can have an effect on passengers' comfort in airplane environments. Low latency has no additional impact on passengers comfort when using hi-tech windows in aircraft cabin. Long latency has an impact on sickness severity mainly characterized by oculomotor symptoms. Subjective evaluation of realness is negative correlated with severity of motion sickness. Seating in an aircraft cabin had no effect on severity of motion sickness under different latency conditions.